2023
DOI: 10.4103/singaporemedj.smj-2022-216
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment landscape for obesity in Singapore

Abstract: The rising prevalence of obesity in Singapore is a harbinger for a corresponding increase in obesity-related complications such as type 2 diabetes mellitus (T2DM) and coronary heart disease. Obesity is a complex disease driven by multiple factors, and hence, treatment cannot follow a ’one-size-fits-all’ approach. Lifestyle modifications involving dietary interventions, physical activity and behavioural changes remain the cornerstone of obesity management. However, similar to other chronic diseases such as T2DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 89 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…Tirzepatide is a dual GLP-1 and glucose-dependent insulinotropic polypeptide (GIP) receptor agonist given as a weekly subcutaneous injection, approved in the US for treatment of T2D in 2022 and for chronic obesity treatment in 2023. A 72-week RCT in participants with obesity and T2D showed a mean weight loss of 15.7% with 15 mg of tirzepatide vs. 3.3% with placebo [68] . (Another similar study in individuals with obesity but without T2D showed mean total weight loss of 16 to 22.5% after 72 weeks' of treatment with tirzepatide 5-15 mg weekly.)…”
Section: Management Of Diabetes In the Chronic Post-operative Phase A...mentioning
confidence: 99%
“…Tirzepatide is a dual GLP-1 and glucose-dependent insulinotropic polypeptide (GIP) receptor agonist given as a weekly subcutaneous injection, approved in the US for treatment of T2D in 2022 and for chronic obesity treatment in 2023. A 72-week RCT in participants with obesity and T2D showed a mean weight loss of 15.7% with 15 mg of tirzepatide vs. 3.3% with placebo [68] . (Another similar study in individuals with obesity but without T2D showed mean total weight loss of 16 to 22.5% after 72 weeks' of treatment with tirzepatide 5-15 mg weekly.)…”
Section: Management Of Diabetes In the Chronic Post-operative Phase A...mentioning
confidence: 99%
“…The most common drugs used to control obesity are orlistat (pancreatic lipase inhibitor), phentermine (sympathomimetic amine), liraglutide (glucagon-like peptide 1 receptor agonist), and naltrexone-bupropion (opioid antagonist and a dopamine and noradrenaline reuptake inhibitor). However, all of them have undesired side effects [30] that can be reduced using natural products from plants as a strategy against obesity [31].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al . [ 12 ] provided a succinct updated summary on the armamentarium of therapeutic tools to target the roots of obesity.…”
mentioning
confidence: 99%